Designing Home Security Monitoring System Based Internet of Things(IoTs) Model - Dedi Satria; Hendri Ahmadian (Jurnal Serambi Engineering, 2018)
The uninhabited housing situation is very vulnerable to the existence of theft activities. Anticipation using a variety of door locking system of the house also often can be overcome by various the perpetrators of theft. Information technology today is inseparable from the development of internet communication technology. The Internet today are an essential part of every society as a means of Informastion Source. Therefore, there needs to be integration of home security system which can be integrated with internet based information system as one of innovation in security system. The research objective is the design and manufacture of sensor-based home security system as a passive infrared motion detectors integrated with Internet-based information system with the concept of the Internet of things (IoTs). The research used Passive Infra Red Sensor as input data, Arduino Uno Microcontroller as Sensor Data Processor and Ethernet as Web Server. The research resulted in a series of home security information system prototype based internet information and has successfully accessed through an Internet browser in the form of home security information to detect the presence of an intruder without permission remotely via the internet.